096 Maintenance IVIg safe prescribing – audit of proforma and traffic light risk assessment system in NHNN. Issue 6 (27th May 2022) - Delaney, Milo; Gillingham, Alexandra; Compton, Laura; Kapoor, Mahima; Lavin, Timothy; Rossor, Alexander; Manji, Hadi; Reilly, Mary; Lunn, Michael; Carr, Aisling
Abstract : Introduction: We recently published safety data on maintenance IVIg therapy for inflammatory neuropa- thies in similar patient cohorts from NHNN and the Manchester Neurosciences group [1, 2]. Based on our findings the following clinical practice changes have been introduced: Routine monitoring and proactive treatment of vascular risk factors A traffic light system for guidance on appropriate blood testing. Methods: Analysis of 2 weeks of IVIg admissions in NHNN prior to and within a month of the introduction of the proforma. Ethics was granted by the clinical governance committee. Results: 69 patient episodes were identified. 63(91.3%)day-care admissions, 6(8.7%)inpatient. 34 female (49.3%).18 patients(26.1%) had bloods taken prior to administration, 60(87%) and 30(43.5%) were screened for symptoms of venous and arterial thromboembolism. 2 (2.9%) and 0 were asked about VTE and ATE risk factors. 63 (91.3%) were asked about infectious symptoms. After introduction of the proforma screening for VTE, TTE and infections symptoms and risk improved to 100%. Aprropriate pre-IVIg bloods were taken in 4(6%). Conclusion: IVIg is effective and low risk therapy for inflammatory neuropathy, however rare and serious complications can occur. We created this proforma to optimise safety monitoring in longterm mainte- nance therapy with reassuring improvements in this pilot review. milo.delaney@nhs.net